Biological effective doses in the intracavitary high dose rate brachytherapy of cervical cancer - Sharma, B. Arunkumar; Singh, Th. Tomcha; Singh, L. Jaichand; Singh, Y. Indibor; Devi, Y. Sobita (Journal of Contemporary Brachytherapy, 2011)
Purpose: The aim of this study is to evaluate the decrease of biological equivalent dose and its correlation with local/loco-regional control of tumour in the treatment of cervical cancer when the strength of the Ir-192 high dose rate (HDR) brachytherapy (BT) source is reduced to single, double and triple half life in relation to original strength of 10 Ci (~ 4.081 cGy x m 2 x h –1 ). Material and methods : A retrospective study was carried out on 52 cervical cancer patients with stage II and III treated with fractionated HDR-BT following external beam radiation therapy (EBRT). International Commission on Radiation Units and Measurement (ICRU) points were defined according to ICRU Report 38, using two orthogonal radiograph images taken by Simulator (Simulix HQ). Biologically effective dose (BED) was calculated at point A for different Ir-192 source strength and its possible correlation with local/loco-regional tumour control was discussed. Result: The increase of treatment time per fraction of dose due to the fall of dose rate especially in HDR-BT of cervical cancer results in reduction in BED of 2.59%, 7.02% and 13.68% with single, double and triple half life reduction of source strength, respectively. The probabilities of disease recurrence (local/loco-regional) within 26 months are expected as 0.12, 0.12, 0.16, 0.39 and 0.80 for source strength of 4.081, 2.041, 1.020, 0.510 and 0.347 cGy x m 2 x h –1 , respectively. The percentages of dose increase required to maintain the same BED with respect to initial BED were estimated as 1.71, 5.00, 11.00 and 15.86 for the dose rate of 24.7, 12.4, 6.2 and 4.2 Gy/hr at point A, respectively. Conclusions: This retrospective study of cervical cancer patients treated with HDR-BT at different Ir-192 source strength shows reduction in disease free survival according to the increase in treatment time duration per fraction. The probable result could be associated with the decrease of biological equivalent dose to point A. Clinical end point of this study is more significant from double half life reduction of original source strength.